TRANSLATION AS A SEMIOTIC INSTRUMENT: A COMPARATIVE STUDY OF CHULPAN’S ORIGINALS AND THEIR TRANSLATIONS - Khushvaktova Gulnoza (Modern American Journals, 2025)
This article explores the intersection of translation and semiotics, emphasizing the evolution of translation studies from marginalization during the structuralist era to its current interdisciplinary relevance. It highlights the shift from form-centered linguistics to an approach that includes meaning, context, and communication. Drawing on semiotic theories and translation analysis, particularly the works of Roman Jakobson and Umberto Eco, the paper demonstrates how translation functions not only as a linguistic operation but also as a semiotic process of interpretation and cultural negotiation.Through comparative analysis of original texts by Abdulhamid Chulpan and their translations into English, the study uncovers implicit meanings and explores how translated versions reshape the language world. The research discusses the challenges of equivalence, including semantic loss, compensation, and cultural adaptation, and considers adequacy from semantic, stylistic, and functional perspectives. The findings reveal how translation bridges linguistic systems and illuminates the translator’s role in cultural transformation.
Keywords: Translation studies, semiotics, poetry, cultural adaptation, equivalence, interpretation, comparative linguistics